2005
DOI: 10.1161/01.cir.0000159329.40098.66
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide–Rich Water Bathing Enhances Collateral Blood Flow in Ischemic Hindlimb via Mobilization of Endothelial Progenitor Cells and Activation of NO-cGMP System

Abstract: Background-Carbon dioxide-rich water bathing has the effect of vasodilatation, whereas it remains undetermined whether this therapy exerts an angiogenic action associated with new vessel formation. Methods and Results-Unilateral hindlimb ischemia was induced by resecting the femoral arteries of C57BL/J mice.Lower limbs were immersed in CO 2 -enriched water (CO 2 concentration, 1000 to 1200 mg/L) or freshwater (control) at 37°C for 10 minutes once a day. Laser Doppler imaging revealed increased blood perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 26 publications
2
68
0
6
Order By: Relevance
“…Using experimental animals, it has been shown that CO 2 immersion results in a NO-dependent increase in collateral blood perfusion, induction of regional VEGF synthesis, and mobilization of endothelial-lineage progenitor cells into the circulation. 9) These results suggest that CO 2 immersion improves subcutaneous microcirculation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Using experimental animals, it has been shown that CO 2 immersion results in a NO-dependent increase in collateral blood perfusion, induction of regional VEGF synthesis, and mobilization of endothelial-lineage progenitor cells into the circulation. 9) These results suggest that CO 2 immersion improves subcutaneous microcirculation.…”
Section: Discussionmentioning
confidence: 84%
“…The CO 2 -enriched water is made with an extra corporeal circulation system (MRE-SPA-MD, Mitsubishi Rayon Engineering, Tokyo, Japan). 8,9) It can instantly enrich 5 L/min of tap water (pH 6.8) with CO 2 (free CO 2 concentration, 1,000 to 1,200 mg/l, pH 4.6). Patients recorded the immersion dates, which were confirmed by the investigators.…”
Section: Carbon Dioxide-enriched Water Bath (Co 2 Immersion)mentioning
confidence: 99%
“…Carbon dioxide baths might represent an effective therapeutic method in the rehabilitation of coronary heart disease, myocardial infarction and stroke, as well as in the treatment of chronic venous insufficiency, inflammatory diseases and functional disorders [2,3]. Carbonated mineral water baths are considered to be effective in the treatment of peripheral vascular disorders [4].…”
Section: Introductionmentioning
confidence: 99%
“…The increased perivascular pO 2 was due to the effect of CO 2 on the oxyhemoglobin dissociation curve. Irie et al [2] demonstrated that CO 2 immersion induced the production of plasma vascular endothelial growth factor (VEGF), resulting in no-dependent angiogenesis associated with the mobilization of endothelial progenitor cells. Hayashi et al [3] showed that CO 2 immersion increased blood flow in feet to a much higher extent than plain water and it improved the limb salvage rate in critical limb ischemia patients without the option of revascularization.…”
Section: Introductionmentioning
confidence: 99%